KELAYAKAN BOOKLET SUBMATERI PEMANFAATAN KEANEKARAGAMAN HAYATI KELAS X DARI PEMANFAATAN TUMBUHAN PANGAN - Fajri, Hayatul; Syamswisna, Syamswisna; Firdawati, Kiki (JURNAL BIOEDUCATION, 2022)
The utilization of biodiversity is one of the sub-materials taught in 10th grade of senior high school. Student understanding of these sub-materials could support by the interesting learning media. Booklet are one of the interesting learning media. This study aims to measure the feasibility of booklet on the sub-material of the utilization of biodiversity for 10th grade of senior high school. The booklet shows the plants diversity utilized as food sources by the people of Mekar Pelita Village, Melawi Regency. The booklet was validated by 5 validators, 2 lecturers and 3 biology teachers. The validation assessment was based on Likert scale and the data analysis was used Lawshe’s formula. The validation results show that the CVI value reaches 0.99 so the booklet is valid and feasible to be used as a learning media in the sub-material the utilization of biodiversity.